Pathological, Immunological, and Hematological Parameters Associated with Experimental Infection of Citrobacter Freundii in Rabbits - S. R. S Al-Eqabi; G. J. K Al-Abedi (Archives of Razi Institute, 2021)
Citrobacter freundii is one of the most important nosocomial opportunistic pathogens, which causes sepsis, as well as different gross and histopathological lesions in various internal organs in humans and animals, especially dogs and fish. This study aimed to investigate the hematological parameters, immunological responses, and pathological effects of the infection induced by the virulent strain of C. freundii on rabbits. A total of 42 rabbits (local breed; male and female), with a mean weight of 1.5-2 kg, were housed under controlled environmental conditions (20±2°C, 14:10 h light: dark cycle) and allowed ad libitum access to food and water. After two weeks of adaption, the rabbits were divided randomly into three groups of 14 animals per group. Group one (G1) received 3×108 CFU/ml of the virulent isolate (intraperitoneally [IP]) of C. freundii. Group two (G2) was injected subcutaneously (SC) with 3×108 CFU/ml of the virulent strain of C. freundii, while group three was IP injected with phosphate buffer saline and considered a negative control group. Results showed the variable gross pathological effects which included hemorrhage, edema, and congestion of visceral organs. Furthermore, the microscopic lesions showed pneumonia due to inflammatory cells infiltration, mainly neutrophils, macrophages, plasmacytes, and lymphocytes, severe interstitial and intra-alveolar edema, extensive pulmonary hemorrhage, emphysema, and atelectasis. The recorded data from the liver samples revealed hepatitis which was characterized by perivascular and periportal leukocyte cuffing, marked centrilobular with periportal necrosis, extensive hepatic edema, and periportal edema in addition to extensive fibrosis in interlobular septa and periportal fibrosis with severe interstitial hemorrhage. In the kidneys, there were severe renal edema, mixed inflammatory exudation, mainly neutrophils, macrophages, plasmacytes, lymphocytes, fibroblast infiltration in renal parenchyma and renal cortex, extensive renal hemorrhage, edema, as well as fibrosis and severe renal tubular necrosis. In addition, enteritis appeared in the intestine with mucosal edema, especially in lamina propria; moreover, necrosis of entire villi, epithelial necrosis, mucosal and submucosal hemorrhage, and fibrosis were observed. The present study revealed a significant increase in total leukocytes count and the concentration of TNF-α in the infected groups. To the best of the authors' knowledge, this study is considered the first attempt aimed to detect the pathological effects of C. freundii on visceral organs in rabbits. It is concluded that this bacterium could induce a significant pathological, hematological, and immunological changes in the infected animals.